An investigation into the effect of mobile poetry-based instruction on the literacy levels of Grade 8 English first additional language learners within the South African rural context : a case study - Bezuidenhout, Marianne M. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.